Perbandingan Algoritma dan Pemetaan Total Suspended Solid di Kawasan Pesisir Indonesia Berdasarkan Data Penginderaan Jauh Berbasis Google Earth Engine - Latifa, Afina; Marsisno, Waris (Politeknik Statistika STIS, 2024)
Indonesia's waters are threatened by marine pollution from various sources, which harms marine ecosystems and human health. Total Suspended Solids (TSS) is a key parameter indicating marine pollution. This study aims to identify the MNDWI threshold value for coastal mapping in Indonesia using remote sensing data, compare TSS calculation algorithms to obtain the most accurate TSS estimates, and map TSS concentrations in Indonesia's coastal areas based on the best TSS algorithm. The collected remote sensing data were analyzed using Normalized Mean Absolute Error (NMAE), Root Mean Square Error (RMSE), and mapping techniques. The research mapped Indonesia's coastal areas with a Modified Normalized Difference Water Index (MNDWI) threshold value ≥ 0.06. The Laili algorithm was found to be the most accurate for TSS calculation, with an NMAE of 2.31% and an RMSE of 20.44. Additionally, TSS concentrations in Indonesia's coastal areas were mapped using the Laili, Liu, and Wijaya algorithms.